On the identity of the species described in the genus Lithobius Leach, 1814 by L. J. Dobroruka from the former Czechoslovakia (Czech and Slovak Republics) (Chilopoda: Lithobiomorpha) - Tuf, Ivan Hadrián; Wytwer, Jolanta; Tajovský, Karel (Zootaxa, 2008)
Type material of the species or subspecies from the centipede genus Lithobius Leach, 1814 found in Dobroruka´s collection, as well as the specimens identified by Dobroruka from the collections of the National Museum in Prague and of the Southern Moravia Museum in Znojmo were revised. As a result, all nine species or subspecies of Lithobius described by Dobroruka from former Czechoslovakia are synonyms of other European species, as follows: Lithobius corrigendus Dobroruka,1988 = Lithobius lucifugus L. Koch, 1862; Lithobius erythrocephalus mohelensis Dobroruka,1959 = Lithobius erythrocephalus C.L. Koch, 1847; Lithobius evae Dobroruka,1958 = Lithobius tenebrosus Meinert, 1872; Lithobius magurensis Dobroruka,1971 = Lithobius muticus C.L. Koch, 1847; Lithobius purkynei Dobroruka,1957 = Lithobius macilentus L. Koch, 1862; Lithobius pusillus johni Dobroruka,1959 = Lithobius lapidicola Meinert, 1872; Lithobius tatricus Dobroruka,1958 = Lithobius mutabilis L. Koch, 1862; Lithobius tatricus monounguis Dobroruka,1958 = Lithobius latro Meinert, 1872; and Monotarsobius homolaci Dobroruka,1971 = Lithobius (Sigibius) burzenlandicus Verhoeff, 1931.